After sales service: the satisfaction of Proton Saga owners / Rosmahadi Mamat @ Mohamed - Mamat @ Mohamed, Rosmahadi (Faculty of Business and Management, 1988)
The consumer today is more discerning - and in making a decision to purchase any product be it cars, electrical or electronic goods - he looks not just for a brand name but more importantly the quality of after sales service. Many a product claiming to have the latest technological innovation has met with a lost in the marketplace because of the manufacturer's or the distributor's inability to ensure an effective after sales service.